2020
DOI: 10.1111/cen.14315
|View full text |Cite
|
Sign up to set email alerts
|

Normocalcaemic primary hyperparathyroidism: An update on diagnostic and management challenges

Abstract: Normocalcaemic primary hyperparathyroidism is a condition that can present with intermittent hypercalcemia or may evolve into hypercalcemic primary hyperparathyroidism. This milder biochemical entity remains incompletely understood because of a lack of long-term health outcomes regarding both medical and surgical approaches to its management. Medical therapies have shown some efficacy. A limited number of studies have found that bisphosphonates increase bone mineral density, and cal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 63 publications
0
17
1
Order By: Relevance
“…These results indicate that chronic PTH over-secretion is implicated in the development of dyshomeostasis on β-cells function, as well as development of insulin resistance in adipose tissue [20]. However, previous clinical human studies have not consistently reported a deterioration of peripheral insulin action [8][9][10]. In this study, no differences in HOMA-IR or HOMA-B indices between groups were evident, probably as a result of the small sample size.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…These results indicate that chronic PTH over-secretion is implicated in the development of dyshomeostasis on β-cells function, as well as development of insulin resistance in adipose tissue [20]. However, previous clinical human studies have not consistently reported a deterioration of peripheral insulin action [8][9][10]. In this study, no differences in HOMA-IR or HOMA-B indices between groups were evident, probably as a result of the small sample size.…”
Section: Discussioncontrasting
confidence: 50%
“…A total of 32 patients with NPHPT and prediabetes were initially included. NPHPT was defined as elevated serum PTH concentration (>65 pg/mL) and normal corrected serum Ca concentration [1,10]. Corrected Ca and PTH concentrations were measured on at least two occasions during a 3-6-month period, to confirm the persistence of the hyperparathyroid state.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is defined as elevated concentrations of calcium (total calcium corrected for albumin level or ionized calcium), elevated parathormone concentration (PTH; or normal, but not suppressed by hypercalcemia) and exclusion of secondary causes of hyperparathyroidism. Normocalcemic PHPT is a condition in which calcium concentration is normal, but PTH is elevated (and secondary causes of hyperparathyroidism are excluded) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%